2012
DOI: 10.1590/s0100-879x2012007500098
|View full text |Cite
|
Sign up to set email alerts
|

Memory mood congruency phenomenon in bipolar I disorder and major depression disorder patients

Abstract: The objective of the present study was to evaluate memory performance in tasks with and without affective content (to confirm the mood congruency phenomenon) in acutely admitted patients with bipolar I disorder (BD) and major depression disorder (MDD) and in healthy participants. Seventy-eight participants (24 BD, 29 MDD, and 25 healthy controls) were evaluated. Three word lists were used as the memory task with affective content (positive, negative and indifferent). Psychiatric symptoms were also evaluated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 33 publications
1
3
2
Order By: Relevance
“…We also report no significant differences between cases and controls or single-episode versus recurrent MDD on vocabulary, also consistent with Snyder et al 4 . However, we were unable to replicate some results previously reported in the literature 5 7 , 10 12 , 28 , 29 . Snyder et al 4 observed significant lower performance in phonemic verbal fluency between cases and controls whereas we observed no significant difference.…”
Section: Discussioncontrasting
confidence: 96%
See 1 more Smart Citation
“…We also report no significant differences between cases and controls or single-episode versus recurrent MDD on vocabulary, also consistent with Snyder et al 4 . However, we were unable to replicate some results previously reported in the literature 5 7 , 10 12 , 28 , 29 . Snyder et al 4 observed significant lower performance in phonemic verbal fluency between cases and controls whereas we observed no significant difference.…”
Section: Discussioncontrasting
confidence: 96%
“…They observed that MDD patients performed significantly less well than controls on both LM immediate and delayed. This result has been previously reported by smaller studies not included in the Lim et al study 10 , 11 , with one exception 12 . Significant lower performances were also observed in the attention domain 6 , via the digit span test and continuous performance test where MDD patients performed slower compared to controls.…”
Section: Introductionsupporting
confidence: 87%
“…In the present study, the presentation of unpleasant stimuli in a blocked manner induced a sustained unpleasant state ( Bradley et al , 1996 ; Pereira et al , 2006 ), and this emotional state biased the representation of unpleasant information in WM ( Grant et al , 2001 ; Siemer, 2005 ; Hammar and Årdal, 2009 ; Brose et al , 2012 ; Delgado et al , 2012 ; Charpentier et al , 2016 ). Accordingly, individuals in unpleasant mood states exhibit an attentional bias towards unpleasant stimuli ( Joormann and Gotlib, 2008 ) and impaired cognitive flexibility, resulting in a cost of maintaining task-relevant items in WM ( Gasper, 2003 ).…”
Section: Discussionmentioning
confidence: 54%
“…Although there is a profusion of research suggesting that mood disorders are prevalent in adults with ADHD (e.g., Fayyad et al, 2007; Garcia et al, 2012; Halmoy et al, 2009; Kessler et al, 2006; Sobanski et al, 2007) and that current mood state affects the accuracy of memories (e.g., Airaksinen, Larsson, Lundberg, & Forsell, 2004; Delgado et al, 2012; Teasdale & Russell, 1983), there does not appear to be any literature to date investigating the issue specific to the present study. This study aims to assess whether self-reported current mood state affects the accuracy of retrospective self-ratings of childhood ADHD symptoms.…”
Section: Introductionmentioning
confidence: 92%
“…There is an abundance of research to suggest that memory performance is often influenced by the affective state of an individual at a given time of testing. For example, depressed individuals are suggested to have a memory bias resulting in a better recollection of negative information, whereas positive words are more easily recalled by individuals with elated moods (Teasdale & Russell, 1983), an ideology known as mood congruency (Delgado, Kapczinski, & Chaves, 2012). Memory is also susceptible to the negativity bias whereby individuals over-exaggerate negative experiences and under-exaggerate positive experiences (Ready, Weinberger, & Jones, 2007).…”
Section: Introductionmentioning
confidence: 99%